Penetrating Trauma in the Pregnant Patient - Lauren Weinberger Conlon; Elizabeth Powell (Association of American Medical Colleges, 2012)
Abstract This resource is a case-based simulation exercise highlighting the management of a pregnant patient involved in penetrating trauma. This educational tool utilizes high-fidelity simulation to take learners through the case. The setting can be described as either an academic trauma center or a community emergency department. The case involves a young female patient suffering a gunshot wound. Participants will be expected to manage the care of this patient after transfer from emergency medical services. This case was created as part of our emergency medicine resident simulation curriculum. This case is based on an actual patient seen in our emergency department and highlights specific teaching points and potential pitfalls in treatment algorithms. The simulation venue offers a unique opportunity to address team dynamics as well as provide a forum for didactic learning as it is often difficult to debrief a critical case while working in real-time patient care settings.